Father's Responsibility for Child Maintenance in Divorce - Marbun, Nismayani; Simamora, Janpatar (Manunggal Halim Jaya, 2025)
The responsibility of fathers for child maintenance in divorce is a crucial issue in family law in Indonesia, regulated by the Civil Code (KUHPerdata) and Law Number 1 of 1974 concerning Marriage. This journal aims to analyze the legal obligation of fathers in providing maintenance to children after divorce, as well as factors that affect their fulfillment. This study uses a normative juridical method with an analytical approach to relevant legal provisions and case studies from court decisions. The results of the study show that fathers have the responsibility to meet the basic needs of children, including food, clothing, shelter, and education, until the child reaches adulthood or can be independent. Despite clear legal provisions, in practice, many fathers do not fulfill their obligations for various reasons, such as difficult economic conditions and a lack of understanding of legal responsibility. The court has an important role in enforcing this maintenance obligation through a fair judgment and in accordance with the father's ability. The study also found that communication between ex-spouses and support from legal institutions is essential to ensure that children's rights are met. It is hoped that the results of this study can be a reference for policymakers and legal practitioners in an effort to improve the protection of children's rights after divorce.